The BRUVs workshop – An Australia-wide synthesis of baited remote underwater video data to answer broad-scale ecological questions about fish, sharks and rays. (May 2021) - Harvey, Euan S.; McLean, Dianne L.; Goetze, Jordan S.; Saunders, Benjamin J.; Langlois, Tim J.; Monk, Jacquomo; Barrett, Neville; Wilson, Shaun K.; Holmes, Thomas H.; Ierodiaconou, Daniel; Jordan, Alan R.; Meekan, Mark G.; et al.
Abstract: Many marine fish populations have declined due to the individual or cumulative impacts of increasing water temperatures, ocean acidification, overfishing and other human-induced impacts such as land run-off, dredging and habitat alteration. Some solutions may be offered by ecosystem-based fisheries and conservation management. However, understanding their effectiveness relies on the availability of good quality data on the size distributions and abundance of fish populations and assemblages, collected at appropriate temporal and spatial scales. Since the early 2000s, baited remote underwater video systems (BRUVs) have become a popular tool for collecting data on fish assemblages across a range of depths and habitats. In Australia, this technique has been adopted by many different agencies and institutions, creating a unique opportunity to compile a continental-scale synthesis of fish data using a standardised sampling technique. Key Australian researchers and managers were invited to contribute to a synthesis workshop on baited underwater video in Albany, Western Australia between the 4th and 8th of February 2018. Data from 19, 939 BRUVs deployments, collected between 2000 and 2017 around Australia, were compiled using GlobalArchive (globalarchive.org). The workshop identified and prioritised several key research themes that would contribute to the conservation and sustainable management of focal species and broad assemblages. Our goal is to describe where and when the data were collected, the type of equipment used and how the imagery was analysed. We also discuss the types of questions that can be addressed by analysing these standardised datasets and the potential benefits to conservation and fisheries management.